Relações entre biomimética, pensamento sistêmico e conhecimento ecológico tradicional: um guia para tomada de decisões arquitetônicas regenerativas - De Nardin, Anna Clara Franzen (2023)
The environmental crisis is in many ways a consequence of design methods incompatible with the long-term maintenance of life on Earth. The need to go beyond sustainability, creating more regenerative practices in architecture, engineering and construction is clear due to the huge impact of these areas on the planet. However, there is a lack of tools that are suitable to the Brazilian context and can guide the decision-making from an integrative perspective. Traditional ways of designing buildings, their metrics and epistemologies are still very much based on observing each part of the building system in isolation, which generally translates into a list of dispersed design solutions to meet each problem. Thus, the development of a regenerative guide that encourages the visualization of interdependencies between decisionmaking criteria becomes necessary. This research aims to enter this blind spot, understanding how regenerative design, biomimicry, systems thinking and indigenous ecological knowledge intersect, and how they can orient the creation of design guidelines that lead the way to a regenerative architectural practice centered on the local context. The method chosen for conducting the research was the Design Science Research, which begins with a systematic and narrative literature review to raise the state of the art in the research theme and define reference artifacts. On this basis, an initial version of the guide will be proposed, with the definition of thematic areas for analysis and establishment of regenerative guidelines, presented graphically through a systemic view, understanding how the criteria interrelate to form a holarchic system. Afterwards, semi-structured interviews will be conducted with indigenous leaders and students of architecture from different ethnicities, aiming to deepen the understanding of traditional ecological knowledge and the human-housing-nature relationship. Finally, the artifact will be evaluated and opportunities for improvement will be identified by conducting an online meeting with the same indigenous representatives, treated here as specialists and co-creators of the tool. The answers will go through an analysis process, and it is hoped that the data gathered in the literature review and interview steps will provide guidance regarding the synthesis of regenerative architectural principles into a framework that facilitates positive decision-making processes in relation to natural, social and economic systems.